2017
DOI: 10.18632/oncotarget.16478
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs in cutaneous melanoma: clinical perspectives

Abstract: Metastatic melanoma of the skin has a high mortality despite the recent introduction of targeted therapy and immunotherapy. Long non-coding RNAs (lncRNAs) are defined as transcripts of more than 200 nucleotides in length that lack protein-coding potential. There is growing evidence that lncRNAs play an important role in gene regulation, including oncogenesis. We present 13 lncRNA genes involved in the pathogenesis of cutaneous melanoma through a variety of pathways and molecular interactions. Some of these lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 95 publications
(136 reference statements)
0
32
0
Order By: Relevance
“…Moreover, many lncRNAs were found to be stable and easily detectable in plasma or other body fluids, highlighting the possibilities of lncRNAs for the diagnostics and treatment of cancer [ 39 ]. Although several lncRNAs have been reported to be involved in the pathogenesis of melanoma, such as BANCR, SLNCR1, CASC15, MALAT1 and so on [ 12 ], genome-wide systematic analysis for the predictive value of lncRNAs in prognosis prediction for cutaneous melanoma is lacking because of limited available lncRNA expression profiles in cutaneous melanoma. Fortunately, Li et al proposed a computational pipeline to obtained genome-wide lncRNA expression profiles in a large number of patients with various cancers by repurposing large-scale RNA-Seq cohorts from TCGA project [ 40 ], thus facilitating the discovery and validation of novel lncRNA biomarkers in some cancers and providing an unprecedented opportunity to systematically evaluate clinical implication for diagnosis and prognosis in cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many lncRNAs were found to be stable and easily detectable in plasma or other body fluids, highlighting the possibilities of lncRNAs for the diagnostics and treatment of cancer [ 39 ]. Although several lncRNAs have been reported to be involved in the pathogenesis of melanoma, such as BANCR, SLNCR1, CASC15, MALAT1 and so on [ 12 ], genome-wide systematic analysis for the predictive value of lncRNAs in prognosis prediction for cutaneous melanoma is lacking because of limited available lncRNA expression profiles in cutaneous melanoma. Fortunately, Li et al proposed a computational pipeline to obtained genome-wide lncRNA expression profiles in a large number of patients with various cancers by repurposing large-scale RNA-Seq cohorts from TCGA project [ 40 ], thus facilitating the discovery and validation of novel lncRNA biomarkers in some cancers and providing an unprecedented opportunity to systematically evaluate clinical implication for diagnosis and prognosis in cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in cancer biology have identified a large number of lncRNAs that are dysregulated expression in the development and tumorigenesis of cancers, highlighting the importance of lncRNAs as a key player for human cancers [ 9 11 ]. Several research groups have focused on expression change of lncRNAs and identified some differentially expressed lncRNAs implicated in the pathogenesis of cutaneous melanoma, revealing the potential of lncRNAs as biomarkers or therapeutic targets for cutaneous melanoma [ 12 , 13 ]. Although many efforts have been made to identify lncRNA signature in a wide range of human cancers [ 14 31 ], the prognostic value of lncRNAs still remains unclear and need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is also mounting evidence to indicate that lncRNAs may play a role in the cancer paradigm ( 5 , 6 ). Increasing attention has been paid to the potential role of lncRNAs in the molecular mechanisms of melanoma ( 7 ). There is evidence to suggest that the lncRNA HOTAIR is linked to melanoma cell motility and invasion ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…No effective treatments are available once this malignant tumour has spread [6][7][8]. The oncogenic transformation of melanocytes to melanoma is the result of complex changes in multiple physiopathological pathways that control cell cycle progression and apoptosis [9]. The identification of treatable diseases that accelerate the progression of melanoma and the pathways involved in this progression can be crucial for reducing the mortality from melanoma.…”
Section: Introductionmentioning
confidence: 99%